Relationship between anthropometrics and handgrip strength among Nigerian school children - Hammed Adebisi I.; Agbonlahor Elvis I. (Sciendo, 2017)
Study aim: Was to investigate the relationship of anthropometrics with handgrip strength (HGS) among Nigerian school children.